Strategic Development of Tourism Taking into Account Regional Features of the Republic of Uzbekistan - Khasan Ibragimovich Turdibekov; Nodirbek Khasanovich Ibrokhimov (Indonesian Journal of Law and Economics Review, 2020)
In this article, the authors examined the features of the strategic analysis of the tourism industry, assessed the new challenges facing the development of the national tourism economy. Using SWOT strategic analysis tools, weaknesses and threats are critically evaluated, and the strengths and opportunities for the development of the tourism industry in a particular region are identified. Long-term strategic management as a management science is reflected in all sectors of the economy. However, the study of strategic planning in the tourism industry in countries that are beginning to move into the post-industrial community has not been fully investigated and determined the course of research. Modern tourism industry is seen as one of the rapidly developing camping industry in international trade in services. Over the past 20 years, the average annual growth rate of the number of arriving foreign tourists in the world amounted to 5.0 %, foreign exchange earnings - 14%, the number of arriving tourists in the world is about 1.4 billion. Today, it is possible to satisfy the rapidly changing needs of tourists by strengthening integration processes both within the tourism system and with the external environment. However, along with the development of tourism, problems of sustainable tourism development arise, develop and become urgent, the solution of which by the methods established in the past becomes inexpedient, which leads to a decrease in the competitiveness of this highly profitable industry, and the lack of tools that make it possible to more fully satisfy the growing demand for high quality travel services. These arguments suggest the need for a systematic approach in the strategic management of tourism and the development of an appropriate strategy for the development of the tourism industry.